Drug therapy in patients with chronic renal failure - Hartmann, Bertram Josef; Czock, David; Keller, Frieder (Deutsches Ärzteblatt, 2010)
Chronic kidney disease (CKD) is divided into five stages; thus, the global term “compensated renal insufficiency” should no longer be used (Table 1 gif ppt). It is important to know whether a patient is suffering from renal insufficiency (CKD stages...